Evolving dynamics of insect frass fertilizer for sustainable nematode management and potato production - Anedo, Emmanuel O.; Beesigamukama, Dennis; Mochoge, Benson; Korir, Nicholas K.; Haukeland, Solveig; Cheseto, Xavier; Subramanian, Sevgan; Kelemu, Segenet; Tanga, Chrysantus M. (Frontiers in Plant Science, 2024)
Potato production faces major challenges from inadequate soil fertility, and nematode infestation, yet synthetic fertilizers and nematicides are costly and harmful to the environment. This study explored the potential of chitin-fortified black soldier fly-composted organic fertilizer (BSFCOF) as a multipurpose organic fertilizer amendment for enhancing potato yield and suppressing potato cyst nematodes (PCN). The BSFCOF was applied at a rate equivalent to 150 kg N ha-1 and fortified with chitin from black soldier fly pupal exuviae at inclusion rates equivalent to 0.5, 1, 2, 3, 4 and 5% chitin. Data were collected on potato growth characteristics, PCN population densities, and soil chemical properties for two growing cycles. Results showed that chitin fortified BSFCOF significantly improved potato growth parameters, chlorophyll concentration, marketable tuber yield and number of marketable tubers. The marketable tuber yield achieved using chitin-fortified BSFCOF was 70 – 362%, and 69 – 238% higher than the values achieved using unfertilized soil during the first and second growing cycles, respectively. Soil amendment with chitin-fortified BSFCOF significantly reduced the number of cysts per 200 g soil-1, number of eggs and J2 per cyst-1, eggs g-1 soil and reproduction rate by 32 – 87%, 9 – 92%, 31– 98% and 31 – 98%, respectively. The PCN suppression increased with chitin inclusion rates. There were significantly higher values for soil pH, ammonium nitrogen, nitrate nitrogen, available phosphorus, calcium, magnesium, potassium, and cation exchange capacity in soil amended with BSFCOF compared to unamended soil. This study demonstrates that BSFCOF fortified with 5% chitin is an effective soil enhancer with multiple benefits, including improved soil fertility, potato performance, and effective management of potato cyst nematodes.